A monoclonal antibody that targets the conserved core/lipid A region of lipopolysaccharide affects motility and reduces intestinal colonization of both classical and El Tor Vibrio cholerae biotypes. Issue 48 (21st November 2016) - Levinson, Kara J.; Baranova, Danielle E.; Mantis, Nicholas J.
Highlights: ZAC-3 is a monoclonal antibody against a conserved Vibrio cholerae epitope. ZAC-3 is an inhibitor of V. cholerae flagellum-based motility. ZAC-3 IgG and Fab fragments reduce V. cholerae intestinal colonization in a mouse model. ZAC-3 reveals potential of antibodies to confer immunity across V. cholerae biotypes. Abstract: Vibrio cholerae is the causative agent of cholera, an acute diarrheal disease that remains endemic in many parts of the world. The mechanisms underlying immunity to cholera remain poorly defined, though it is increasingly clear that protection is associated with antibodies against lipopolysaccharide (LPS). Here we report that ZAC-3, a monoclonal antibody against the core/lipid A region of V. cholerae LPS is a potent inhibitor of V. cholerae flagellum-based motility in viscous and liquid environments. ZAC-3 arrested motility of the classical Ogawa strain O395, as well as the El Tor Inaba strain C6706. In addition, we demonstrate, in the neonatal mouse model, that ZAC-3 IgG and Fab fragments significantly reduced the ability of both V. cholerae strains O395 and C6706 to colonize the intestinal epithelium, revealing the potential of antibodies against the core/lipid A to contribute to immunity across biotypes, possibly through a mechanism involving motility arrest.